Exploring the Experiences of Senior High School Students on Business Simulation in the New Normal: Basis for a Proposed Intervention Program - Amper, Edlyn C. (Future Science / FSH-PH Publications, 2022)
Work immersion is a subject in senior high school that is being taught to prepare learners for their future endeavors. As part of the preparation of the Department of Education to secondary students for work, entrepreneurship, and higher education. Immersion can also help students strengthen their skills or expertise, preparing them for future careers. This study is a qualitative research study that focuses on the business simulation experiences of Senior High School students in the midst of pandemics. The main purpose of this study is to determine the different components that contribute to Entrepreneurial sustainability through business simulation in work immersion subjects and to assess the long-term implications of the entrepreneurial desire of learners to engage in small businesses for senior high school students in time of Covid-19 pandemic and to provide The proposed intervention is not simply focused on the school; the data gathered from the students is heavily influenced by the community. The schools, in collaboration with the teachers, lead learners through their school activities, preparing them to meet the obstacles they will face as they enter the profession. The school can aid the learner in preparing their product and assisting with the planning stage of their business simulation activity. Learners' business simulations require community assistance to be effective. The students urge for support structure that the community and local government can provide in the form of product marketing, patronage, and financial support to encourage aspiring entrepreneurs like the learners to keep their small businesses running.